Chatbots and Government Communications in Covid-19 Pandemic - Untari, Ika Meilani (JURNAL KOMUNIKASI INDONESIA, 2020)
COVID-19 has forced the world to change. Indonesian government, like the rest of the global community, promptly responded to the soaring transmission rate by launching an app to cater the Indonesians’ need for information. COVID19 GO.ID was launched on March 20, 2020, adding to previous chatbots built by WHO and afterwards followed by GOV UK. Using casestudies method and comparing it to the four unique affordances of chatbot, this study wasconducted to com pare the three chatbots, and thus achieve a valuable information to improve Indonesia’s chatbot under the Media Richness Theory. Indonesian government chatbot needs to add more engaging and informative topics. The availability of shareable graphics and videos would add richness to the chatbot, as well topics that provide information on myth buster or hoax revelation, mental health support and how people can donate to the society. COVID-19 telah memaksa dunia berubah. Pemerintah Indonesia, seperti komunitas global lainnya, segera merespon tingginya angka penularan dengan meluncurkan sebuah aplikasi untuk menjawab kebutuhan informasi masyarakat Indonesia. COVID19 GO.ID diluncurkan pada20 Maret 2020, menambah daftar chatbot yang telah dibangun oleh WHO, dan kemudian diikutioleh GOV UK. Dengan menggunakan metode studi kasus dan membandingkannya dengan empat kemampuan chatbot, kajian ini dimaksudkan untuk membandingkan ketiga chatbot tersebut dan menghasilkan informasi berharga untuk memperbaiki chatbot pemerintah Indonesia menggunakan Teori Kekayaan Media. Chatbot pemerintah Indonesia perlu menambahkan topik yang lebih melibatkan masyarakat dan lebih informatif. Ketersediaanmedia infografis dan video yang mudah didesiminasikan akan menambahkan kekayaan terhadap chatbot, begitu pula topik yang membahas mitos atau mengupas tentang hoaks, dukungan kesehatan mental dan bagaimana masyarakat dapat berdonasi.